Development of a Ramayana-based Counseling Module for Persons with Common Mental Health Disorders - Chhaya Shantaram Kurhade; Aarti Jagannathan; Shivarama Varambally; Sushrutha Shivana; Paulomi Sudhir; B. N. Gangadhar (Indian Journal of Psychological Medicine, 2025)
Background: Common mental health disorders (CMDs) affect nearly 10% of the population, with the majority (80%) remaining untreated. Culturally relevant counseling approaches can be a means to reach many untreated persons. We describe the development and validation of a socioculturally relevant counseling module based on the Ramayana for persons with CMDs. Methods: The study employed an exploratory research framework to design the counseling module. The module underwent a comprehensive review of the Valmiki Ramayana to ensure its cultural relevance. Content validation was performed by mental health professionals from the field of Indian psychology. Concurrently, a panel of 15 experts from diverse backgrounds in Indian psychology validated the counseling module based on the Ramayana . Results: Based on the results of expert interviews ( n = 15), the counseling techniques, encompassing concepts, anecdotes, and narratives, were finalized. These interviews also contributed to the refinement of the counseling module. The primary objective of the content validation process was to systematically assess the appropriateness, accuracy, and practicality of the various components within the module. The content validation demonstrated that all items contained within the module exceeded the established threshold of p = .59. Conclusions: The developed counseling module based on the Ramayana is feasible to be implemented as a sociocultural intervention for persons with CMDs. By assisting persons to enhance coping abilities and improve overall well-being, this module offers a valuable resource for mental health intervention in the Indian sociocultural context. It fosters a culturally sensitive and practical approach to address the diverse mental health needs of the population.